Analyzing external and internal membrane fouling by oil emulsions via 3D optical coherence tomography - Trinh, Thien An (2020)
Membrane-based filtration is an emerging technique for processing oily wastewater. Improving the efficiency of oil-water separation via membranes entails novel techniques for studying the complex interactions between the oil droplets and membrane underlying fouling. This paper presents the first study that applies optical coherence tomography (OCT) to the characterization of membrane fouling by oil emulsions. A series of dead-end filtration experiments was performed to characterize the rejection of oil droplets (~ 10 µm; hexadecane) by the membrane structure (0.45 µm PVDF) via three-dimensional (3D) OCT scanning in real time. The experimental results were compared with the control experiments with ~ 10 µm glass beads to identify the optical artifacts. Both the external and internal fouling by the oil droplets were successfully revealed by analyzing the variation in OCT intensity at various layers that were mathematically defined in terms of the coordinate surfaces parallel to, and above and below, the feed-membrane interface. The evolution of membrane fouling was quantified by evaluating the fraction of fouling voxels as a function of time at varied depths. This study demonstrates that the OCT-based characterization has the potential to shed light on the complex interactions occurring in oil-water separations via membrane filtration, particularly by providing real-time non-invasive monitoring of internal fouling, the understanding of which is valuable for both fundamental research and practical applications.